The Comparison of Physical Fitness Levels Among Participants of Extracurricular Activities: Male Futsal and Basketball at SMA Negeri 21 Surabaya - Adikara, Wresniwira Bima; Wisnu, Hari (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
In a school environment, there must be a program that can increase the talents and interests of each student. This program is an extracurricular that is useful for improving students' talents in academic and non-academic activities. An example is developing talent in students who have an interest in sports activities. At SMA Negeri 21 Surabaya, the sports that students are interested in are basketball and futsal. But every extracurricular definitely has participants with different physical abilities. Students' physical abilities can be determined by carrying out a physical fitness test through one of the VO2max tests. The purpose of providing VO2max is to find out whether futsal and basketball extracurricular participants have different levels of physical fitness. Measurement of physical fitness level uses a bleep test where extracurricular participants will run according to the sound made by the instrument. Each level gets faster for the sound. After measuring the level of physical fitness for each extracurricular activity, the measuring tool used to determine differences in physical fitness levels is SPSS 26. The results of the research that has been carried out show that the results of physical fitness levels are almost the same. Because the results of the independent sample t-test do not show a result of 0.000, The results of the calculation show 0.293, which is not said to have a significant difference in the level of physical fitness of futsal and basketball extracurricular participants at SMA Negeri 21 Surabaya.